A single biochemical activity underlies the pleiotropy of the aging-related protein CLK-1 - Ju-Ling Liu (Nature Portfolio, 2017)
Abstract The Caenorhabditis elegans clk-1 gene and the orthologous mouse gene Mclk1 encode a mitochondrial hydroxylase that is necessary for the biosynthesis of ubiquinone (UQ). Mutations in these genes produce broadly pleiotropic phenotypes in both species, including a lengthening of animal lifespan. A number of features of the C. elegans clk-1 mutants, including a maternal effect, particularly extensive pleiotropy, as well as unexplained differences between alleles have suggested that CLK-1/MCLK1 might have additional functions besides that in UQ biosynthesis. In addition, a recent study suggested that a cryptic nuclear localization signal could lead to nuclear localization in cultured mammalian cell lines. Here, by using immunohistochemical techniques in worms and purification techniques in mammalian cells, we failed to detect any nuclear enrichment of the MCLK1 or CLK-1 proteins and any biological activity of a C. elegans CLK-1 protein devoid of a mitochondrial localization sequence. In addition, and most importantly, by pharmacologically restoring UQ biosynthesis in clk-1 null mutants we show that loss of UQ biosynthesis is responsible for all phenotypes resulting from loss of CLK-1, including behavioral phenotypes, altered expression of mitochondrial quality control genes, and lifespan.